Bioeconomic comparison of breed types Holstein, Jersey and Holstein×Jersey in Costa Rica. - Vargas-Leitón, Bernardo (2012)
The objetcive of this work was to compare the bioeconomic performance of Holstein, Jersey and F1 Holstein×Jersey cattle from the Premontane Wet Forest lifezone in Costa Rica. According to the model, an average Holstein cow produces 448 and 1393 kg of milk per year above the F1 or Jersey cow, respectively. An average F1 cow produces 24 and 115 more kg of milk solids than the Holstein or Jersey cow. On an average herd with 80 adult cows, the F1 is expected to produce 3863 and 382 kg more kg of milk solids than Holstein or Jersey. An average Holstein herd is expected to produce 667 and 1468 more kg of meat per year than an F1 or Jersey herd. The expected annual income for an F1 herd is US$20644 and US$34434 higher than a Holstein or Jersey herd. The expected annual cost for the F1 herd is US$3697 and US$10848 higher than a Holstein or Jersey herd. Expected gross margin for the F1 herd is US$16946 and US$23586 higher than a Holstein or Jersey herd. Expected benefit/ cost ratio for the F1 herd was 0,10 and 0,15 higher than a Holstein or Jersey herd. Variables with positive significant effects on benefit/cost ratio were the production level, lactation length, fat and protein content, cows/milkmen ratio and herd size. Variables with negative significant effects on benefit/cost were days open, base salary for agricultural workers and price of concentrate.